MaRIUS land use - Janes, Victoria (Cranfield University, 2017)
Outputs of the IAP2 batch simulation with a range of precipitation and temperature perturbations.See article "Dynamic response of land use and river nutrient concentration to long-term climatic changes".
Keywords: land use'; 'modelling'; 'climate change'; 'Land Use and Environmental Planning'; 'Environmental Science'; 'Climate Change Processes'